RISK FACTORS FOR THE OCCURENCE OF CARDIOVASCULAR DISEASES - Stojanović, Marko (Medicinski podmladak, 2024)
According to the World Health Organization (WHO) report from 2018, cardiovascular diseases (CVD) with 17.9 million deaths had a share of as much as 41% among the causes of mortality from non-communicable diseases with a representation of 31% in all causes of mortality. With a share of 45% of all deaths annually, i.e. 3.9 million, CVD is the leading cause of death in Europe according to the latest data from the European Heart Disease Network. Mortality is slightly higher in the female population with 2.1 million or 49%, compared to men with 1.8 or 40% of the causes of death. According to the latest published data According to the latest published data from the Institute for Public Health of Serbia "Dr. Milan Jovanović Batut" from 2018, mortality caused by CVD in Serbia is estimated at 51.8%, and due to poor implementation of preventive measures, Serbia is classified as a high-risk country. Non-modifiable risk factors for CVD are: age, gender, age, ethnicity and family history. Modifiable risk factors include: high systolic blood pressure, high low-density lipoprotein (LDL), dietary risks, high glucose, tobacco smoking (active and passive), high body mass index (BMI), low level of physical activity, kidney dysfunction, excessive alcohol use, lead exposure, air pollution, high or low temperatures. Prevention and treatment of CVD is based on lifestyle modification, dietary intervention, improvement of physical activity and eventual use of medications. A minimum intake of 500 grams of fruit and vegetables per day is recommended, limiting salt intake to less than 5 grams per day, limiting sugar and fat intake to 10% and 30% of total energy intake, as well as balancing between total energy intake and energy consumption. The results of the PRIMED study showed significant positive effects of the Mediterranean diet on the primary prevention of CVD. The recommended physical activity is 150 minutes of moderate to high intensity physical activity per week, 75 minutes of high intensity physical activity per week, or the equivalent of a combination of moderate and high intensity physical activity.